Feminisation of Terrorism: Legal and Policy Implications for Sustainable Development - Owolabi, Fadeke Esther; Ekong, Idongesit Daniel (Journal of Law & Policy Review, 2025)
The increasing participation of women in terrorist activities has reshaped contemporary violent extremism and altered the operational dynamics of extremist networks. This study aims to examine the nature, patterns, and implications of the feminisation of terrorism, with particular attention to its legal, security, and developmental consequences. The study employs a qualitative research design, based on a content analysis of secondary data, including international security reports, terrorism incident databases, and peer-reviewed scholarly literature on female involvement in groups such as Boko Haram and al-Qaeda affiliates. The analysis identifies a growing diversification of women’s roles within terrorist organisations, including recruitment, logistics, intelligence gathering, and operational participation, which enhances the tactical flexibility of these groups and complicates traditional counter-terrorism responses. These dynamics undermine national security, weaken social cohesion, and threaten progress toward sustainable development, particularly in conflict-affected societies. The study concludes that existing counter-terrorism and legal frameworks are insufficiently responsive to the gendered dimensions of violent extremism and recommends the adoption of integrated, gender-sensitive legal, policy, and crisis-management strategies to improve prevention, accountability, and long-term developmental outcomes.